Acne treatment: research progress and new perspectives - Li, Yuwei; Hu, Xinhong; Dong, Gaohong; Wang, Xiaoxia; Liu, Tao (Frontiers in Medicine, 2024)
Acne is a chronic inflammatory skin disease that primarily affects adolescents and is attributed to various factors, including hormonal changes, genetic predisposition, and environmental influences. It typically manifests in areas rich in sebaceous glands such as the face, chest, and back. Symptoms of acne can range from mild to severe and may present as pimples, pustules, nodules, cysts, and scarring. The appearance of acne can significantly impact both the physical and mental well-being of patients, potentially leading to feelings of anxiety, depression, and social withdrawal. The pathogenesis of acne is multifaceted involving genetic predisposition as well as environmental factors such as hormonal imbalances, inflammation, abnormal follicular sebaceous unit keratinization, proliferation of follicular microorganisms like Propionibacterium acnes, increased sebum production, and dietary influences. Traditional treatment methods for acne include topical drug therapy, oral drug therapy, photoelectric therapy, and chemical peeling. With ongoing research into the pathogenesis of acne, treatment methods are rapidly evolving with novel antibiotics, probiotics, biological agents, topical anti-androgen drugs, topical vitamin A acid metabolism blockers, antimicrobial peptides, immunotherapy, micro-needling, and micro-needling patches. This article aims to provide a comprehensive review of recent advancements in acne treatment.